Differential efficacy of bioagents against Fusarium udum isolates - and R.G. CHAUDHARY, VISHWA DHAR*, S. MISHRA (Indian Phytopathology, 2006)
Efficacy of saprophytically competitive bioagents against Fusarium udum was studied in vitro at the Indian Institute of Pulses Research, Kanpur during 2000-2001 using dual culture technique on potato dextrose agar medium. Three bioagents viz., Trichoderma viride (TNAU, Coimbatore), T. harzianum (GBPUA&T, Pantnagar) and Gliocladium virens (GBPUA&T, Pant Nagar) were evaluated against ten isolates of F.udum obtained from research farm of IIPR, Kanpur. The three bioagents varied in their efficacy in relation to F. udum isolates. After 96 hours of inoculation low colony growth was recorded in F10 , F12, F14 and F17 isolates (16.6-18.6 mm) in the presence of T. viride while least growth of F14 (16.0 mm) was obtained with T. harzianum. The colony growth of F10 was on par (18.3-19.0 mm) with all three bioagents. T. harzianum was found growing saprophytically fast in the presence of ten F. udum isolates in dual culture. After 96 hrs of incubation, the percent reduction of ten isolates of F. udum ranged between 35.5-54.8 against T. viride, 36.4-54.7 against T. harzianum and 36.4-57.3 against G.virens. Population counts of F.udum isolates and bioagents from the parasitized colonies after 7 days of inoculation using dilution technique revealed at par population in F13 and F14 . G. virens recorded highest population in the presence of F8 while T. viride and G. virens showed at par population in F10 .